NITRIC ACID TRANSPORT FROM THE STRATOSPHERE TO THE TROPOSPHERE AND ICE SHEET IN ANTARCTICA THROUGH POLAR STRATOSPHERE - イワサカ, ヤスノブ; ハヤシ, マサヒコ; IWASAKA, Yasunobu; HAYASHI, Masahiko (National Institute of Polar Research, 1991)
P(論文) Growth and sedimentation of polar stratospheric clouds (PSCs) particles are examined using a numerical model named the 'Test Particle Sedimentation Model'.PSCs particles transport stratospheric nitric acid (HNO_3) to the troposphere (maybe near the ice sheet) for several days by their sedimentation. The amounts of HNO_3 and H_2O removed by a particle depends on the trajectory of the particle (length of path and residence time). Usually the removed amount is larger in the higher part of the PSCs layer comparing with the lower part of the layer. The features of HNO_3 transport are consistent with the results of chemical analyses of the Antarctic ice sheet and of aerosols sampled at the surface of the ice sheet. departmental bulletin paper